The Role Of Influencers And Lifestyles In Influence Purchase Intention Of Shoppe And Tik –Tok Shop Users - Deviana Indah Sari (EKONOMI DAN BISNIS DIGITAL, 2022)
Purpose of this article: . In this study, it aims to see how much influence influencers and lifestyle have in influencing the purchase intention of marketplace usersMethodology The use of data in this study uses the IBM SPSS 25 for windows application with several stages of statistical testing through a distribution of 100 respondentsResult : The results of this study influencer and lifestyle simultaneously have a positive effect on the purchase intention of marketplace users, influencers partially have a positive effect on the purchase intention of marketplace users and lifestyle partially have a positive effect on the purchase intention of marketplace users.Keywords: Influencer, Lifestyle And Purchase Intention